RETRACTED: Prevailing and emerging cyber threats and security practices in IoT-Enabled smart grids: A survey. (15th April 2019) - Gupta, Abhishek; Anpalagan, Alagan; Carvalho, Glaucio H.S.; Khwaja, Ahmed S.; Guan, Ling; Woungang, Isaac
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief and Authors. We regret to announce that we must retract this article because errors have been identified in the publication involving several parts of the study. Three missing references should have been added throughout the manuscript [145] S. Yasir; C. Noel; R. M. Husain, C. Rebecca, "Open Access Internet of Things-aided Smart Grid: Technologies, Architectures, Applications, Prototypes, and Future Research Directions", available athttps://arxiv.org/ftp/arxiv/papers/1704/1704.08977.pdf . [146] J. Mendel, http://www.e-mentor.edu.pl/eng/article/index/number/68/id/1282 [Accessed: 16-11-2018]. [147] Belden, https://wireless.electronicspecifier.com/around-the-industry/cyber-security-for-tsn-in-modern-automation-networks [Accessed: 01-04-2018] Moreover, Fig. 2 and 3 should have been cited with [145], Fig. 7: should have been cited with [146] and Fig. 13 and 14: should have been cited with [147]. We regret any problems that this article may have caused.